Finger millet as a carbon source for biofloc, improved growth performance of Pangasianodon hypophthalmus (Sauvage, 1878) fingerlings - Nageswari, P.; Verma, A. K.; Gupta, Subodh; Jeyakumari, A. (Indian Journal of Fisheries, 2020)
A 90-days experiment was conducted to investigate the effects of biofloc produced with different carbon sources on growth performances, survival and body indices of Pangasianodon hypophthalmus fingerlings (average body weight: 6.4±0.05 g). The different carbon sources used in the experiment employing biofloc technology (BFT) were BFT-T (tapioca), BFT-S (sorghum), BFT-PM (pearl millet), BFT-FM (finger millet) and clear water with no addition of carbon source was treated as control. At the end of the experiment, significantly (p<0.05) higher weight gain (24.34±0.50 g), Specific growth rate, SGR (1.37±0.02% day-1); Feed efficiency ratio, FER (0.47±0.01); Protein efficiency ratio, PER (1.47±0.03) and lower Feed conversion ratio, FCR (2.12±0.03) were witnessed in the group where finger millet was used as a carbon source (BFTFM) and significantly lower responses were noticed in the control (CW). Results showed that there were no significant differences (p>0.05) in hepatosomatic index and viscerosomatic index of fish between the different experimental groups. During the termination of the experiment, no mortality was seen among the different experimental groups. Based on the results acquired from this study, finger millet could be used as an ideal carbon source for biofloc to augment the growth and productivity of P. hypophthalmus under farming. Keywords: Biofloc, Carbon source, Finger millet, Fish culture, Sutchi catfish